The portrait of Istanbul in 1922 as extracted Aydede (man in the moon) comics periodical - Yazıcıoğlu, Ayşe, 1976- (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This thesis scrutinizes the portrait of Istanbul as extracted from Aydede comics periodical. Aydede is a political comics periodical published during the Armistice period. The political, social and economic developments of Istanbul were examined by searching the articles and the cartoons of Aydede. In this context, the Armistice period and the life story of Refik Halid were put in the background of the main question. The conclusion of the thesis consists of the rapid and deep social changes and the response of Aydede comics periodical to the issue, the daily problems of the residents of Istanbul, how the different groups were affected by the economic distress and the criticism towards to the notables of politics and literature.
Keywords: Turkish periodicals -- History.; Turkish wit and humor -- Periodicals.; Turkish literature -- Periodicals.; Turkey -- Politics and government -- Anecdotes -- Periodicals.